Migration Studies: How Should We Approach Them? Learning Through Participatory Practices. The So-Close Case Study. (9th December 2022) - Gunella, Chiara; Rodrigo, Javier
Community members such as migrants are involved to collect data but not included in the actual research process, for example, in developing research guidelines or in using research tools such as data analysis. Participatory methodology enables investigating a specific issue while including the community involved. In the So-Close project, we applied this approach to investigate how we study migration and the role of the cultural heritage of forced migration through four multi-stakeholders participatory focus groups (FGs) in Spain (involving Refugees, NGO and Cultural Institutions representatives, Academics and Policy-Makers). From the FGs, emerged the need to investigate complex issues from various angles and contexts to create sustainable, community-approved, and shared solutions.